Risk factors and outcome of delayed graft function after cadaveric kidney transplantation: A report from the Thai transplant registry - N. Premasathian (2018)
Introduction Kidney transplantation is the best treatment for end-stage renal disease patients. Delayed graft function (DGF) remains one of the major problems after cadaveric kidney transplantation. This study has reported the risk factors and outcomes of DGF using data from Thai Transplant Registry Database. Methods The data of all cadaveric kidney transplantations (CD-KT) were retrieved from the database. DGF was defined as a failure to decrease the serum creatinine within 72 hours or a requirement for dialysis within the first week after transplantation. We performed logistic regression analysis to correlate donor features (age, sex, cardio-pulmonary resuscitation (CPR), brain death from a cerebrovascular accident (CVA), best and last serum creatinine) with recipient demographics (age, sex) and clinical outcomes cold ischemic time [CIT] and DGF. Results We analyzed 756 CD-KT including 320 (42%) patients experiencing DGF. Upon multivariate analysis, factors significantly correlated with DGF were CIT (P < .001), donor last serum creatinine (P < .001), interleukin 2 monoclonal antibody induction (P = .004), donor age (P = .017), donor CVA (P = .012), and prior peritoneal dialysis (PD) (P = .012). There was no significant correlation between DGF and donor height, weight, sex, CPR, brain death from CVA, best serum creatinine, recipient age, or sex in multivariate analysis. Graft survivals at 1 and 5 years after transplantation were significantly lower among the DGF group namely, 91.0% vs. 95.2% and 78.7% vs. 86.0%, respectively (P = .006). Patient survival was also significantly lower 94.1% vs. 96.4% and 82.1% vs. 92.2%, respectively, (P = .001). Conclusion A higher value of the donor's terminal serum creatinine, CIT, IL2mAb induction, PD prior to KT and donor age increased the risk for DGF after CD-KT. DGF significantly lowered kidney allograft and patient survivals at 1 and 5 years after transplantation among the Thai population. © 2010 Elsevier Inc. All rights reserved.